Sublittoral Macrobenthic Communities of Storfjord (Eastern Svalbard) and Factors Influencing Their Distribution and Structure - Lyudmila V. Pavlova; Alexander G. Dvoretsky; Alexander A. Frolov; Olga L. Zimina; Olga Yu. Evseeva; Dinara R. Dikaeva; Zinaida Yu. Rumyantseva; Ninel N. Panteleeva; Evgeniy A. Garbul (Animals)
Seafloor communities along the eastern Svalbard coast remain poorly studied. To address this gap, we sampled benthic organisms on the soft sediments of Storfjord in 2017 and 2019, a large fjord predominantly influenced by cold Arctic waters, to study the local fauna and identify the key environmental drivers shaping community structure. In total, 314 taxa were recorded, with an increase in abundance (from 3923 to 8977 ind. m−2, mean 6090 ind. m−2) and a decline in biomass (ranging from 265 to 104 g m−2, mean 188 g m−2) toward the outer part of the fjord. However, no clear spatial trends were observed for alpha diversity (approximately 100 species per 0.3 m2) or the Shannon index (mean 3 per station). The primary factors influencing benthic abundance were the duration of the ice-free period (IFP) and the degree of siltation (DS), both of which are proxies for trophic conditions. The prevailing taxa displayed a high tolerance to temperature fluctuations and seasonal variability in nutrient inputs. Benthic biomass showed a negative relationship with IFP, DS, and water depth, but it was positively correlated with the proportion of fine-grained sediment. The Yoldia hyperborea community (mean abundance: 3700 ind. m−2, mean biomass: 227 g m−2) was associated with Arctic waters characterized by higher inorganic suspension loads. In contrast, areas with reduced or weaker sedimentation were dominated by the communities of Maldane sarsi (6212 ind m−2, 226 g m−2) and Maldane sarsi + Nemertini g.sp. (5568 ind m−2, 165 g m−2). The Spiochaetopterus typicus community (7824 ind m−2, 139 g m−2) was observed in areas under moderate influence of Atlantic waters, characterized by low sedimentation rates and increased fresh detritus flux.